Effect of Learning Outcomes in the Second Class of College Students in China on Core Competencies: Taking Learning Self-efficacy as a Moderator - Chen, Lu-Xi; Chen, Liang (Journal of Ecohumanism, 2024)
This study used learning self-efficacy as a Mediator to examine the effect of learning outcomes in the second class on core competencies of university students. The researchers developed a structural equation model and a research hypothesis using the second class learning outcomes scale, learning self-efficacy scale and core competencies scale. After analysis, the 3 scales had sufficient reliability, validity, and fit. The researchers distributed electronic questionnaires of the “second class report card” to students in 6 pilot universities in Guangxi Province, China, and participants responded using 5-point Likert-type scales. The researchers collected 2133 valid questionnaires. The results of the analysis showed that university students’ learning outcomes in the second class is a positive predictor of their core competencies, and learning self-efficacy partially mediator the influence of learning outcomes in the second class on core competencies. Therefore, improving Chinese university students’ learning outcomes in the second class may improve their core competencies, and second class can have a positive effect on core competencies through learning self-efficacy. University administrators and teachers should enhance the learning self-efficacy of university students and promote their core competencies.